THE OPINIONS OF GRADUATES CONCERNING THE IMPACT OF PARTICIPATING AND NOT PARTICIPATING IN STUDENT ACTIVITIES ON THE WORKING BEHAVIORS AFTER GRADUATIONS - หิรัญสุข นพพร; ปิ่นเจริญ สถาพร (Business Administration and Management Journal Review, 2013)
The purpose of this paper is to explore graduate’s perceptions of the impact of their participation or non participation in student activities. The paper considers whether participation or non participation has any effect on working behaviors after graduations and aims to bring the results of this study to help better motivate students to participate in activities and finally to help faculty members and the university management plan for student activities which are related to student wants now and in the future. The methodology of this research is qualitative using in-depth interviews for twenty people. This paper explores a result in which it was revealed that there is a difference in the team work of graduates who participate and those who do not participate. Graduates who participate in student activities have better human relationship and greater collaboration than those who do not participate because those who participate were trained to work as a team during student activities. Additionally, there is significance in the leadership factor where by the participating student have better creative thinking and self confident because they feel familiar with team work and the group meeting atmosphere from their involvement in student activities. For further research, this research should be integrated into a real business sector for giving graduating students experiences to be ready for an affective employee after they graduated.